The application of unmanned aerial vehicle for measuring greening sustainable residential: Tree canopy mapping / Suzanah Abdullah ... [et al.] - Abdullah, Suzanah; Tahar, Khairul Nizam; Abdul Rashid, Mohd Fadzil; Osoman, Muhammad Ariffin; Hassan, Khalilah (2021)
Trees and plants play an important role in promoting a greening-sustainable residential environment. They keep cool, fresh and beautiful environments and subsequently, make people healthier, happier, safer and more productive. As a key indicator of green space planning, there is a need to measure it. The current paper attempts to measure tree canopy cover in residential neighborhood areas by using GIS-based Unmanned Aerial Vehicle (UAV). To seek for the purpose, Puncak Iskandar has been selected for the case study. The study has found that many types of tree canopy have been planted along streets, but they were not sufficient enough according to the residents' size. This paper provides a significant measure and relevant findings to assist urban planners or stakeholders in planning and managing trees in particular in the case study and urban areas in general, towards promoting greening- sustainable living environment.